Seed morphology of the genus Scrophularia L. (Scrophulariaceae) from Turkey and its taxonomic implications - Özbek, Funda; Uzunhi̇sarcikli Mehmet Erkan; Eki̇ci̇ Murat; Güner, Ebru Doğan; Pinar, Nur Münevver (Phytotaxa, 2020)
73 taxa of the genus Scrophularia (Scrophulariaceae) from Turkey have been investigated using light stereomicroscope (LM) and scanning electron microscopy (SEM) in order to describe their seed morphological characteristics and to evaluate the diagnostic value of these features as a contribution to the genus systematics. The seeds are oblong, ellipsoid, ovoid or obovoid in shape and light or dark brown, blackish-brown to black in colour. The seed length ranges from 0.41 to 2.04 mm and seed width from 0.24 to 1.33 mm. All investigated taxa have bireticulate-alveolate ornamentation with vesicles on the corners of secondary reticulum cells except of S. zuvandica. The alveoli are oblong, orbicular and linear with a size of 7.63–143.1 × 21.62–314.2 µm. Cluster analysis and principal component analysis have been used to determine the contribution of seed morphological characters to the taxa relationships. Numerical analysis has revealed that the seed size and the secondary reticulum properties have significant importance in taxonomy of the genus for distinguishing taxa from each other.